Regularity and Stability in Monotone Bayesian Games - Beggs, A (Department of Economics (University of Oxford), 2011)
This paper denes regular and weakly regular equilibria for monotone Bayesian games with with one-dimensional actions and types. It proves an index theorem and provides applications to uniqueness of equilibrium. It also provides analyses of stability with respect to perturbations and dynamic stability.